Horizontal crank position affects economy and upper limb kinematics of recumbent handcyclists - Stone, B.; Mason, B. S.; Warner, M. B.; Goosey-Tolfrey, V. L. (Medicine & Science in Sports & Exercise, 2019)
PURPOSE: To determine the effects of horizontal crank position on economy and upper limb kinematics in recumbent handcycling.